Visual Deprivation Decreases Somatic GAD65 Puncta Number on Layer 2/3 Pyramidal Neurons in Mouse Visual Cortex. (25th May 2009) - Kreczko, Alicja; Goel, Anubhuthi; Song, Lihua; Lee, Hey-Kyoung
Abstract : Proper functioning of the visual system depends on maturation of both excitatory and inhibitory synapses within the visual cortex. Considering that perisomatic inhibition is one of the key factors that control the critical period in visual cortex, it is pertinent to understand its regulation by visual experience. To do this, we developed an immunohistochemical method that allows three-dimensional (3D) analysis of the glutamic acid decarboxylase (GAD) 65-positive inhibitory terminals in the visual cortex. Using this method on transgenic mice expressing yellow fluorescence protein (YFP) in a subset of neurons, we found that the number of somatic GAD65-puncta on individual layer 2/3 pyramidal neurons is reduced when mice are dark-reared from birth and reverted to normal levels by re-exposure to light. There was no change in GAD65-puncta volume or intensity. These results support the reorganization of inhibitory circuitry within layer 2/3 of visual cortex in response to changes in visual experience.